PENGARUH APLIKASI SMARTPHONE SEBAGAI MEDIA PENUNJANG PEMBELAJARAN KANJI TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Windy Puspita Sari; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The use of smartphone applications as a supporting medium for learning kanji can help Japanese learners overcome difficulties when learning kanji. The purpose of this study was to describe the use of smartphone applications as a medium to support kanji learning and to describe the correlation between the use of smartphone applications as a medium to support kanji learning and the final grades of the kanji subjects for Japanese Language Study Program students, Faculty of Teachers Training and Education Riau University. The method used was descriptive quantitative method. The data shows that students use a type of digital dictionary application, especially in the reading feature kanji. Most students use this application for the purposes of doing class assignments and looking for the meaning of kanji vocabulary when reading / hearing something within 1 hour or less than 1 hour. Based on the results of hypothesis testing, it was found that the use of a smartphone application as a supporting medium for kanji learning had a positive effect on kanji learning outcomes of students.Key Words: Smartphone aplication, learning outcomes, kanji, learning support media